Prediction of Damage Cost of Bronchitis Due to Haze in Malaysia - Mohd Khairul Amri, Kamarudin; Noorjima, Abd Wahab; Khalid, Abdul Rahim (2016)
Awareness of haze pollution and management increased in Southeast Asia since 1990. However, the focus on environmental management is decreasing especially in Malaysia due to the abundant resources and increased development pressure. The total health damage cost because of haze in the country became significantly high due to the long duration of haze events year by year. This paper discusses the health damage caused by bronchitis due to the haze events in Malaysia. The analysis shows positive coefficient of independent variables which indicates the positive relationship between dependent variable and independent variables. Multiple linear regression analysis shows that 45.3% variation in damage cost of bronchitis could be explained by FAI, GDPPC, and CO2.